2017
DOI: 10.1177/2167696817712809
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Parental Psychological Control and Warmth in College Students’ Relational Aggression and Friendship Quality

Abstract: This study investigated the role of perceived parental psychological control and warmth in college students' friendship quality and use of relational aggression with peers. College students (N ¼ 237) completed self-report measures assessing their relational aggression, friendship quality, and parents' perceived use of psychological control and warmth. As predicted, college students' relational aggression partially mediated the relation between perceived parental psychological control and friendship quality. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Still, hearing status might influence regulation capabilities and one's likelihood to engage in aggressive behavior (e.g., Babaroglu, 2016), though these differences were not examined in the present study. Additionally, given that samples of similar studies on relational aggression in emerging adults have reflected similar demographics as the present study (e.g., Baumgardner & Boyatzis, 2018), further work would benefit from examining a similar model of relational aggression in more diverse samples.…”
Section: Discussionmentioning
confidence: 90%
“…Still, hearing status might influence regulation capabilities and one's likelihood to engage in aggressive behavior (e.g., Babaroglu, 2016), though these differences were not examined in the present study. Additionally, given that samples of similar studies on relational aggression in emerging adults have reflected similar demographics as the present study (e.g., Baumgardner & Boyatzis, 2018), further work would benefit from examining a similar model of relational aggression in more diverse samples.…”
Section: Discussionmentioning
confidence: 90%
“…At the opposite, parental psychological control is consistently associated with maladjustment and ill-being (Soenens & Vansteenkiste, 2010). Previous studies have shown, in fact, positive relations with depressive symptoms (Bleys, Soenens, Claes, Vliegen, & Luyten, 2018), frustration intolerance (Filippello, Harrington, Costa, Buzzai, & Sorrenti, 2018) and relational aggression (Baumgardner & Boyatzis, 2017). Although abundant research emphasized the importance of parental psychological controlling and autonomy-supportive behaviours for adolescent emotional development, evidence on the association between parental psychological control, parental autonomy support and trait EI is limited (Gugliandolo et al, 2015a).…”
Section: Parental Autonomy Support and Psychological Controlmentioning
confidence: 99%
“…For instance, Zhao et al (2021) conducted a cross-sectional study in Chinese adolescents, and found that positive parenting was positively associated with friendship quality. Baumgardner and Boyatzis (2017) conducted a cross-sectional study among college students, and found that parental psychological control was negatively associated with friendship quality. Moller et al (2019) has also found that parental conditional regard was negatively associated with security of attachment with friends, which was used as an indicator of relationship quality.…”
Section: The Associations Between Parenting Practices and Adolescent ...mentioning
confidence: 99%